Exploring the role of additive manufacturing in the prosthetic supply chain: qualitative evidence - Al-Masa’fah, Wasan; Abushaikha, Ismail; Bwaliez, Omar M. (Emerald, 2025)
Purpose This study aims to evaluate the enhancement in prosthetic supply chain capabilities resulting from the implementation of additive manufacturing (AM) technologies. The study presents an emerging model outlining the key areas that undergo changes when integrating 3D printing technologies into the prosthetic supply chain. Design/methodology/approach Employing a qualitative approach, data were collected through field observations and 31 in-depth interviews conducted within various Jordanian organizations associated with the prosthetic industry and 3D printing technologies. Findings The findings suggest that the adoption of 3D printing technologies improves the prosthetic supply chain’s capabilities in terms of customization, responsiveness, innovation, environmental sustainability, cost minimization and patient empowerment. The study sheds light on the specific areas affected in the prosthetic supply chain following the adoption of 3D printing technologies, emphasizing the overall improvement in supply chain capabilities within the prosthetic industry. Practical implications This study provides recommendations for governmental bodies and prosthetic organizations to maximize the benefits derived from the use of 3D printing technologies. Originality/value This study contributes as the first of its kind in exploring the impact of 3D printing technology adoption in the Jordanian prosthetic industry, elucidating the effects on the supply chain and identifying challenges for decision-makers in an emerging market context.
Keywords: Additive manufacturing; Supply chain; Prostheses; Prosthetic supply chain; 3D printing; Jordan; 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; Generic health relevance; 9 Industry, Innovation and Infrastructure; 12 Responsible Consumption and Production; Business & Management; 3507 Strategy, management and organisational behaviour